2019
DOI: 10.3390/cells9010023
|View full text |Cite
|
Sign up to set email alerts
|

Functional Compartmentalization of HSP60-Survivin Interaction between Mitochondria and Cytosol in Cancer Cells

Abstract: Heat shock protein 60 (HSP60) and survivin reside in both the cytosolic and mitochondrial compartments under physiological conditions. They can form HSP60-survivin complexes through protein-protein interactions. Their expression levels in cancer tissues are positively correlated and higher expression of either protein is associated with poor clinical prognosis. The subcellular location of HSP60-survivin complex in either the cytosol or mitochondria is cell type-dependent, while the biological significance of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 63 publications
(120 reference statements)
0
37
0
Order By: Relevance
“…On the one hand, Caspase3 is a major executioner caspase, active Caspase3 degrades multiple cellular proteins and is responsible for cell morphology changes and DNA fragmentation during apoptosis [19,20]. On the other hand, HSP60 released from mitochondria to cytosol upon death stimuli might exert a pro-death function, either through stabilizing Bax, enhancing Caspase3 activation, or increasing protein ubiquitination [21,22]. Moreover, Qiu et al, pointed that IGFBP-6 could inhibit invasion and migration of CRC cells possibly via promoting apoptosis activity and arresting cell cycle [23].…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, Caspase3 is a major executioner caspase, active Caspase3 degrades multiple cellular proteins and is responsible for cell morphology changes and DNA fragmentation during apoptosis [19,20]. On the other hand, HSP60 released from mitochondria to cytosol upon death stimuli might exert a pro-death function, either through stabilizing Bax, enhancing Caspase3 activation, or increasing protein ubiquitination [21,22]. Moreover, Qiu et al, pointed that IGFBP-6 could inhibit invasion and migration of CRC cells possibly via promoting apoptosis activity and arresting cell cycle [23].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reported showed that survivin is predominantly localized in the cytoplasm of cancer cells and is generally believed to function as apoptotic suppressor to maintain survival of cancer cells. In contrast, the smaller fraction of nuclear localized survivin is considered to act as a component of CPC complex to promote cell cycle progression, suggesting that the different subcellular pools of survivin exhibit distinct biological functions (13)(14)(15)(16). Thus, as an oncoprotein that is both essential for mitosis and apoptosis inhibition, survivin seemed a promising novel target for anti-cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…released from mitochondria to cytosol upon death stimuli might exert a pro-death function, either through stabilizing Bax, enhancing Caspase3 activation, or increasing protein ubiquitination [21,22]. Moreover, Qiu et al, pointed that IGFBP-6 could inhibit invasion and migration of CRC cells possibly via promoting apoptosis activity and arresting cell cycle [23].…”
Section: Discussionmentioning
confidence: 99%